Kajian Produktivitas Alat Berat di Proyek Jalan Bebas Hambatan Serang-Panimbang KM 27+100 Sampai dengan 30+100 - Hartanto, Bilhan Gamaliel; Rumbyarso, Yonas Prima Arga (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The success of the project depends on human resources and heavy equipment, which is also beneficial in the agriculture, forestry and mining sectors. Heavy equipment users must understand their use efficiency, maintenance costs, and specifications to maximize profits. Proper selection of heavy equipment is critical, as mistakes can hamper projects. The trend of using heavy equipment has a significant effect on infrastructure development, speeding up the process and improving quality. The most optimized and productive period to complete this project is approximately 110 days, this project uses operational vehicles for production such as the following: vibration roller, tandem roller, motor grader, asphalt finisher, dump truck, wheel loader, hydraulic excavator, pneumatic tired roller. The project requires operational vehicles for production as follows: 2 pneumatic tired rollers, 2 hydraulic excavators, 8 dump trucks, 2 motor graders, 2 wheel loaders, 2 vibration rollers, 3 tandem rollers, 2 asphalt finishers.